Introduction and transmission of SARS-CoV-2 via producing and trading activities of cold chain food: current situation and countermeasures - LI Fengqin; LI Ning (Zhongguo shipin weisheng zazhi, 2022)
The outbreak of Coronavirus Disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has significantly affected the people's health and life. The nucleic acid of SARS-CoV-2 in swabbing samples of the environments of food animal slaughterhouses, food processing plants, as well as foods and their inner or outer packaging has been detected. Particularly, the live virus being isolated from frozen foods has aroused the global public concern on whether cold chain foods can act as a carrier in transmission of SARS-CoV-2. In this article, the role of cold chain food in transmitting SARS-CoV-2 together with the risk of professional practice are reviewed